Abstract model power field electromagnetic type building. Part 1 - Igor Pavlovich Popov (Наука. Инновации. Технологии)
It is shown that the classical model of the magnetic field allows the violation of Newton's third law, eliminates interference elements coaxial conductors with currents, does not provide for the existence of moments of forces acting on the elements of the conductors, Ampere's law is considered to be the formula generally incompatible with its main findings. The formal model is an analogue of the electromagnetic field, not having these features in this model meets the essential requirements Ampere - unconditional implementation of Newton's third law.